2012
DOI: 10.1021/pr300368h
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Spectroscopy of Serum Reveals Unique Metabolic Fingerprints Associated with Subtypes of Surgically Induced Osteoarthritis in Sheep

Abstract: Osteoarthritis (OA) is a highly prevalent joint disease. Its slow progressive nature and the correlation between pathological changes and clinical symptoms mean that OA is often well advanced by the time of diagnosis. In the absence of any specific pharmacological treatments, there is a pressing need to develop robust biomarkers for OA. We have adopted a nuclear magnetic resonance (NMR)-based metabolomic strategy to identify molecular responses to surgically induced OA in an animal model. Sheep underwent one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 21 publications
1
38
0
2
Order By: Relevance
“…Our findings provide evidence that the metabolic profile detected in the SF is robust for identifying 2 weeks post‐injury joints as evidenced by the high account of variance (R2Y) and predictive ability (Q2) of the supervised PLS‐DA model. It has already been reported that knee surgery itself might induce very detectable metabolic changes . The lack of separation between the samples collected from idealized ACL reconstruction joints and sham‐surgical joints in the unsupervised PCA model confirms that the major source of variation in the dataset (surgical and non‐surgical samples taken together) can be related to the inflammation and very similar initial joint injury/damage in the first 2 weeks after the surgery.…”
Section: Discussionmentioning
confidence: 70%
“…Our findings provide evidence that the metabolic profile detected in the SF is robust for identifying 2 weeks post‐injury joints as evidenced by the high account of variance (R2Y) and predictive ability (Q2) of the supervised PLS‐DA model. It has already been reported that knee surgery itself might induce very detectable metabolic changes . The lack of separation between the samples collected from idealized ACL reconstruction joints and sham‐surgical joints in the unsupervised PCA model confirms that the major source of variation in the dataset (surgical and non‐surgical samples taken together) can be related to the inflammation and very similar initial joint injury/damage in the first 2 weeks after the surgery.…”
Section: Discussionmentioning
confidence: 70%
“…77 In another study, synovial fluid of MMP-2 was detected 2 and 4 weeks postoperatively in a temporomandibular joint (TMJ) model of OA in sheep. 78 Moreover, MMP-2 activity correlated with initial articular cartilage destruction rather than with the progression of OA.…”
Section: Sheepmentioning
confidence: 98%
“…In fact the protective effects of MSM can be seen as far back as 1991, when Murav’ev and colleagues described the decreased knee joint degeneration of arthritic mice [150]. Interestingly, endogenous serum MSM becomes elevated in sheep post-meniscal destabilization caused osteoarthritis [151]; however, the magnitude of this physiological response was not large enough to protect against cartilage erosion.…”
Section: Common Usesmentioning
confidence: 99%